Population dynamics of Empetrum hermaphroditum(Ericaceae) on a subarctic sand dune: Evidence of rapid colonization through efficient sexual reproduction - Boudreau, Stéphane; Ropars, Pascale; Harper, Karen Amanda (American Journal of Botany, 2010)
The importance of sexual reproduction for clonal plant species has long been underestimated, perhaps as a consequence of the difficulty in identifying individuals, preventing the study of their population dynamics. Such is the case for Empetrum hermaphroditum , an ericaceous species, which dominates the ground vegetation of subarctic ecosystems. Despite abundant seed production, seedlings are rarely observed. Therefore, prevalent seedling recruitment on a subarctic dune system provided an opportunity to study the population dynamics and spatial pattern of the colonization phase of this species. We established a 6‐ha grid on the dune systems that extended from the shoreline to the fixed dunes and mapped and measured all E. hermaphroditum individuals in the grid. Moreover, we sampled 112 individuals just outside the grid to identify any allometric relationship between the size and age of the individuals, which allowed us to reconstruct population expansion. The overall size structure suggests that the population is still expanding. In the last 50 yr, E. hermaphroditum advanced more than 200 m in the dune system. Expansion started in the 1960s simultaneously at different distances from the shoreline. Colonization did not proceed gradually from the fixed dune toward the shoreline but instead individuals established earlier in the troughs between the dunes, with an increasingly clumped spatial pattern as the population filled in with time.